2013
DOI: 10.1007/s10710-013-9186-9
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting meta-learning and hyper-heuristic research: the role of evolutionary algorithms

Abstract: The fields of machine meta-learning and hyper-heuristic optimisation have developed mostly independently of each other, although evolutionary algorithms (particularly genetic programming) have recently played an important role in the development of both fields. Recent work in both fields shares a common goal, that of automating as much of the algorithm design process as possible. In this paper we first provide a historical perspective on automated algorithm design, and then we discuss similarities and differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 95 publications
(42 citation statements)
references
References 98 publications
0
42
0
Order By: Relevance
“…This then makes the design of systems for streaming data tasks especially challenging. One potential path for addressing this, albeit not yet considered in the wider literature, is through evolving hyper-heuristics (or the evolution of the evolutionary algorithms), e.g., [148]. Current research has not considered this avenue, so we revisit the opportunity in the context of future research (Sect.…”
Section: Discussionmentioning
confidence: 99%
“…This then makes the design of systems for streaming data tasks especially challenging. One potential path for addressing this, albeit not yet considered in the wider literature, is through evolving hyper-heuristics (or the evolution of the evolutionary algorithms), e.g., [148]. Current research has not considered this avenue, so we revisit the opportunity in the context of future research (Sect.…”
Section: Discussionmentioning
confidence: 99%
“…As Pappa et al (2013) point out, it can be generally observed, that research efforts in different fields including operations research, optimization, and machine learning ultimately evolved from algorithm / parameter selection and control to the automated generation of algorithms. The combination of simulation-based optimization and evolutionary computation allows performing a search in the space of possible policies by trial and error interactions with a simulation model (Whiteson 2012).…”
Section: Simulation-based Evolution Of Waiting Strategiesmentioning
confidence: 99%
“…Nevertheless, hyper-heuristics usually employ typical metaheuristics (e.g., evolutionary algorithms) as the search methodology to look for suitable heuristics to a computational problem [31].…”
Section: Background On Hyper-heuristicsmentioning
confidence: 99%